Value of FNAC in Diagnosis of Different Types of Thyroiditis and Its Comparison with Clinical and Biochemical Findings (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):250-4.The abstract of this article is available on the PubMed website